4G : LTE/LTE-Advanced for Mobile Broadband - Dahlman, Erik (Elsevier, 2014)
This book reflects the ongoing success of LTE throughout the world and focuses on LTE with full updates including LTE-Advanced (Release 11) to provide a complete picture of the LTE system. Overviews and detailed explanations are given for the latest LTE standards for radio interface architecture, the physical layer, access procedures, broadcast, relaying, spectrum and RF characteristics, and system performance. Key technologies presented include multi-carrier transmission, advanced single-carrier transmission, advanced receivers, OFDM, MIMO and adaptive antenna solutions, advanced ra.